German Society of Nuclear Medicine procedure guideline on beta-amyloid brain PET imaging - Barthel, Henryk; Meyer, Philipp T.; Drzezga, Alexander; Bartenstein, Peter; Boecker, Henning; Brust, Peter; Buchert, Ralph; Coenen, Heinz. H.; La Fougere, Christian; Gruender, Gerhard; Gruenwald, Frank; Krause, Bernd J.; et al. (Nuklearmedizin-Nuclear Medicine, 2016)
Recently, a number of positron emission tomography (PET) radiotracers have been approved for clinical use. These tracers target cerebral beta-amyloid (A?) plaques, a hallmark of Alzheimer's disease. Increasing use of this method implies the need for respective standards. This German Society of Nuclear Medicine guideline describes adequate procedures for A? plaque PET imaging. It not only discusses the tracers used for that purpose, but also lists measures for correct patient preparation, image data generation, processing, analysis and interpretation. With that, this "S1" category (according to the German Association of the Scientific Medical Societies standard) guideline aims at contributing to quality assurance of nuclear imaging in Germany.
EVALuna2:13865